2023
DOI: 10.1002/mawe.202200297
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties and curing features of polymer materials filled with biowaste

Abstract: Besides mechanical properties, the dynamic mechanical properties in a sensible range of temperature and rheological properties have to be taken into account for engineering applications. The rising concern towards the reduction in the use of petroleum-based non-renewable resources has led to increasing interests in natural polymer composites filled with natural organic fillers, i. e. they are from renewable and biodegradable sources. This work is focused on the use of biowaste, specifically wood flour as a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Based on the graphical comparison of the results of the optimum cure time (t 90 ) as shown in Figure 5, it is evident that the values of the optimum cure time (t 90 ) increased for the rubber compounds in comparison to the reference compound R. The most significant increase can be observed for the rubber compound containing the filler modified by plasma with 30 wt% (Ben/P_30) content. From an economic standpoint, this increase in the optimum cure time (t 90 ) translates to higher energy costs [23]. The longer curing time required for the rubber compounds, especially those with plasma-treated bentonite filler and higher 30 wt% content, would result in increased energy consumption during the curing process, potentially impacting production costs.…”
Section: Curing Parameters Of Rubber Compoundsmentioning
confidence: 99%
“…Based on the graphical comparison of the results of the optimum cure time (t 90 ) as shown in Figure 5, it is evident that the values of the optimum cure time (t 90 ) increased for the rubber compounds in comparison to the reference compound R. The most significant increase can be observed for the rubber compound containing the filler modified by plasma with 30 wt% (Ben/P_30) content. From an economic standpoint, this increase in the optimum cure time (t 90 ) translates to higher energy costs [23]. The longer curing time required for the rubber compounds, especially those with plasma-treated bentonite filler and higher 30 wt% content, would result in increased energy consumption during the curing process, potentially impacting production costs.…”
Section: Curing Parameters Of Rubber Compoundsmentioning
confidence: 99%
“…The results revealed that the presence of alternative carbon-based filler ACB obtained lower M L in compare with sample filled with carbon black (N339). M L refers to the viscosity (stiffness) of the rubber compounds [20,21]. During vulcanization period, the decrease in torque was caused by the decrease in the cross-linking of the rubber matrix.…”
Section: Cure Characteristicsmentioning
confidence: 99%